Psychometric Evaluation Of The Malay Version Of The Multidimensional Beck Youth Inventories-2 (BYI-2 Malay): Measuring Self-concept, Anxiety, Depression, Anger, And Disruptive Behaviour Among Adolescents In Sheltered Homes - Wai-Eng Ding; Kit-Aun Tan; Jia-Yuin Fam; Firdaus Mukhtar; Munn-Sann Lye; Hamidin Awang; Khadeeja Munawar (Universiti Putra Malaysia Press, 2024)
Indexed by ERA/MyCite